Simultaneous endoscopic management of urethral duplication and postposterior sagittal anorectoplasty urethral diverticulum in a boy with anorectal malformation - Simmi K Ratan; Chiranjiv Kumar; Satish Kumar Aggarwal (Wolters Kluwer Medknow Publications, 2021)
We report a case of urethral duplication with high anorectal malformation (ARM). A 12-year-old boy who had undergone transverse colostomy on day 2 of life and posterior sagittal anorectoplasty (PSARP) for ARM (rectobulbar fistula) at 8 years and also had urinary dribbling from a midscrotal opening in addition to normal voiding, presented with recurrent urinary tract infections and dysuria. Midscrotal dribbling had continued postoperatively. Colostomy had been closed 3 months after PSARP. Investigations revealed a large urethral diverticulum at the site of rectourethral fistula due to a segment of the gut being left behind during fistula closure. In addition, he had a sagittal urethral duplication originating at bulbar urethra and opening externally at midscrotum. The highlight of this report is successful endoscopic management of both the urethral duplication and the diverticulum.